Collaborative Learning to Improve Creative and Critical Thinking Skills: From Research Design to Data Analysis - Abdul Rahman; Siti Masitoh; Andi Mariono (INTERNATIONAL JOURNAL OF EDUCATIONAL REVIEW, 2022)
This study aims to examine in-depth articles that highlight collaborative learning to improve creative and critical thinking skills, which are published in scientific journals in the field of education in Indonesia. The research conducted includes a type of literature review. The sources of data used in this study were taken from scientific journals accredited by Science and Technology Index (SINTA). The search was limited to articles published from 2017 to 2022. Researchers then reviewed, analyzed, and discussed the content together to evaluate, compile, and refine the reported findings. Among the ten publications, quantitative research with a quasi-experimental design was found to be the most popular. In addition, high school students were chosen the most as research subjects; while the scope of science and mathematics was the most widely used subject, the collaborative model is the most widely applied treatment and is proven to improve students' creative and critical thinking skills; while the test and t-test were the most dominant instruments used for the collection and analysis of research data. The application of research results encourages schools or educational institutions to use collaborative learning models and can be used as evaluation material for various stakeholders who carry out collaborative learning. Several recommendations have been proposed for future research concerning the findings of this study, including the need to increase the diversity of research types that support creative and critical thinking skills as the main focus. It is necessary to increase the frequency of qualitative research on the development of creative and critical thinking skills. It is recommended that researchers choose a more appropriate data analysis technique.